IMPLEMENTATION OF PROJECT-BASED LEARNING MODEL IN MERDEKA BELAJAR CURRICULUM TO IMPROVE STUDENTS’ ENGLISH LEARNING OUTCOMES - Tiara Fahira Putri Army; Dina Irmayanti Harahap (National Conference on Language, Education, and Technology Proceeding, 2023)
Merdeka Belajar Curriculum is a form of evaluation of the previous curriculum, namely the 2013/K-13 curriculum. In Merdeka Belajar Curriculum, students are focused with various intra-curricular learning, where the learning contents presented to students will be more optimal with the aim that students can have enough time to explore concepts and strengthen their competence. So, a learning model is needed to support this curriculum's implementation. Project-based learning model is regarded as a learning model which is suitable to be to implemented in Merdeka Belajar Curriculum. The aim of this study was to investigate how problem-based learning implemented in Merdeka Belajar Curriculum to improve students’ English learning outcomes. The designed of this research was classroom action research in which the data collection was obtained through planning, acting, observation, reflection and tests. The subject of this study was the students grade XI at one of vocational school in North Sumatera which consisted of 30 students. The data analysis technique used qualitative and quantitative that was conducted in 2 cycles. The results showed that the implementation of project-based learning in Merdeka Belajar Curriculum could improve students’ English learning outcomes. It can be seen from the average score of Students’ learning outcomes in cognitive domain at the first cycle from 57.12% increased into 82.88% in the second cycle, the average score of students ‘learning outcomes in psychomotor domain at the first cycle from 53.65% increased into 84.61%, and the average score of students’ learning outcomes in affective domain at the first cycle from 72.5% increased into 83.85%. It showed that the implementation of the project-based learning model in Merdeka Belajar Curriculum can improve students’ English learning outcomes.